2021
DOI: 10.3390/ijerph18126505
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of and Government Planning and Responses to Pandemics for People with Disability: A Rapid Review

Abstract: Objective—To collate evidence on (1) the risk of infection for people with disability during infectious disease outbreaks and/or pandemics and (2) government responses and pandemic plans for people with disability. Methods—Through two rapid reviews, relevant peer-reviewed studies and grey literature published from 2002 onwards in the English language were identified. Data were synthesised narratively. Results—Aim 1: Of the 680 studies, two studies were included in the review. No grey literature was eligible fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…People with disabilities problems and their relationship with social exclusion, labour market and human resources are issues that have been increasingly studied in recent years, highlighting the work of [1,7,10,23,35,36] or [37], among others.…”
Section: Disability Labour Inclusion and Social Stigma: A Behavioral ...mentioning
confidence: 99%
See 1 more Smart Citation
“…People with disabilities problems and their relationship with social exclusion, labour market and human resources are issues that have been increasingly studied in recent years, highlighting the work of [1,7,10,23,35,36] or [37], among others.…”
Section: Disability Labour Inclusion and Social Stigma: A Behavioral ...mentioning
confidence: 99%
“…According to [5,6], this situation is similar in the main European countries, also related to low employment rates. Further, the problem may be getting even worse as a result of the current COVID-19 pandemic, with high impact for people with disabilities [7].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is observed that these innovative programs create opportunities for social inclusion, showing the participants more confidence and independence (highlighting the importance of developing early vocational socialization programs) [84]. 16 USA 2020…”
Section: Australia 2017mentioning
confidence: 99%
“…People with disabilities (PWD) have to face an even worse situation. The current COVID-19 pandemic is affecting PWD more negatively [15,16]. This group starts from a situation weighed down by a series of stigmas, prejudices in the perception and discrimination of the rest of the population [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation